CHALLENGES TO TEA PRODUCTION AND TEA MARKETING IN TARABA STATE OF NIGERIA - Yetunde Olasimbo Mary OLADOKUN; Kayode Akanni OLUYOLE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tea Camellia Sinensis (L) Kuntze is from the family of Theaceae. Tea plant encompasses some 200 woody plants species in the warmer regions of Asia and South America. Tea in its natural habitat develops to a small plant producing flower at six years or less or more based on type of variety and means of propagation. Total area of land under tea cultivation in the world is about 2,600,000 hectares with 86% in Asia, 85% in Africa and the remainder across South America, Russia and Oceania. The highest producer of tea in the world is Asia (60%), followed by Africa(12%). The countries in Africa which are large tea producers are Kenya, Malawi, Burundi and Cameroon. Nigeria still produces tea in small quantities as compared to Kenya. This study therefore examined the challenges to tea production and tea marketing in Taraba State of Nigeria. When these challenges are met tea production will be boosted and probably exported to improve the country’s economy. The study was carried out in Taraba state in Nigeria. Data was collected through the administration of well-structured questionnaire among tea producers and marketers (272). Proportion to size sampling technique was used. In Taraba state, three communities were selected namely Mayo-Kusuku, Kakara and Kasalasah. Based on the population of tea farmers 90, 90, 92 were selected respectively from the communities. The result revealed that, thirty six percent of tea producers were between 17-30 years old, 50% of the producers were between 31-60years while 15% were above 60years. Majority of the producers are male(92.7%) while 7.3% were female. Twenty four percent of the producers have no formal education while seventy six percent have either primary, secondary or tertiary education. The challenges faced include poor soil fertility, low yield, pest infestation, labour shortage, lack of finance and lack of fertilizer/pesticide. Eighty six percent of tea producers lacked finance while 83.8% lacked fertilizer/pesticide. The problems faced by tea marketers in Taraba State are low market demand, low price, lack of access to market and high cost of transportation. Seventy five percent of tea marketers faced the problem of low market demand. Tea producers and marketers in Taraba State have great potential for development. Tea business can bring about economic development in Taraba State and Nigeria as a whole if government at various levels can put in place intervention programmes to overcome these challenges.